Pedagogia da Identidade: interculturalidade e formação de professores - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This research lies on the importance of the cultural identity as a subject to be considered during the formation of the teachers, focused on cultural differences under the view of interculturality in the course of Pedagogy. Such course would be based on the understanding of various epistemologies as different knowledges. The main argument of the research assumes that the work focused on cultural identity in the training of teachers takes for granted the formation of a teaching identity, which is a determining factor on the teacher’s role concerning the cultural differences on the teaching of those children who live in the Amazon. It has been structured on the following problematic: how does the work focused on the cultural identity in the initial formation of the teacher make possible the (re)construction of a teacher identity to deal with the different kinds of culture in the school, considering the development of intercultural education in Parintins, in the Amazon? In order to achieve this goal, the aims of this research were the following: to know the cultural conception and cultural identity that have been the basis to the discourses and practices of the professors in the Federal University of Amazon, in Parintins (ICSEZ), in the Pedagogy course, and how such conception determines the work focused on the cultural differences in the initial teachers training process; to describe the cultural groups that constitute the identities of the Parintinian people from the historical construction of the city and identification of the teachers under formation; to identify how the knowledge of the local cultural identity is worked out in the curriculum and in the practice of the professors of the course of Pedagogy in the ICSEZ, and if such professionals contribute to a teacher training, focused on the work with the cultural differences in the perspective of interculturality; and to analyze the challenges and possibilities of developing a teacher training that considers the local cultural identity, committed to the issues of cultural differences in the perspective of interculturality. The research assumes theoretical assumptions of the critical interculturalism for the teacher formation, conducted by postcolonial contributions. Regarding the methodology, the research assumes the perspective of critical hermeneutics as an approach to understanding the object of study, as it examines in detail the nexuses between the subjects' daily experiences and the cultural representations of these experiences. It has a qualitative nature, and was carried out at the Institute of Social Sciences, Education and Animal Science of Parintins, whose subjects were both the professors and the teachers under formation in the course of Pedagogy. In order to collect data, the following technics have been used, such as direct observation, semi-structured interview, questionnaire and documentary analysis. After that, one comes to the conclusion that the cultural identity of the Parintinense people passes through the indigenous culture, the riverside inhabitants, the city life, the religion, the rite of the boi-bumbá and the contact with those who arrive from other regions of Brazil and the world. However, there is no systematized scientific work focused on the knowledge of the local culture in the course of Pedagogy in Parintins. The ones concerning cultural differences, however, are based on the perspective of liberal multiculturalism, since the monocultural and universalizing character is predominant in the texts, speeches and practices of many professors. Thus, we defend the thesis that in the formation of teachers there should be a work focused on the cultural differences, considering the interculturality, in order to confront the formation of essentialized identities, and to open some gaps for the construction of hybrid, critical and plural educational identities. We are aware that reinventing and deconstructing settler processes is not an easy task; it requires, among other things, confronting challenges and building possibilities as an ethical ideal embedded in the lives of teachers and teachers under formation, who give priority to the formation of open minded people for democracy and social justice.
Keywords: Pedagogia; Identidade Cultural; Interculturalidade; Formação de Professores; CIENCIAS HUMANAS: EDUCACAO